The refusal of secrets: exercise of rights and access to public archives (Tempo e Argumento, 2013)
Thousands of secret government registers relative to many countries were published in recent years at the Internet through WikiLeaks. This polemic action gives the opportunity to discuss, in this article, some historical aspects of the access to public archival documents, their use for the production of historical knowledge and their relevance to citizenship and to consolidate democratic practices. The debate about archival appraisal and its relationship to archival documents access are also briefly discussed.
Keywords: archival documents; public archives; citizenship; archival science; archives - history